EVALUASI KEPUASAN PENGGUNA APLIKASI ILANG JARINGAN MENGGUNAKAN METODE EUCS (END USER COMPUTING SATISFACTION) DI DINAS KOMUNIKASI, INFORMATIKA DAN STATISTIKA - Jihan Khoirun Nisa; Anisa Fadilah Lakepo; Moh. Ramdhan Arif Kaluku; Indhitya R. Padiku (Diffusion: Journal of Systems and Information Technology, 2023)
This Network Loss information system was created to assist employees of the Gorontalo Province Kominfo Service and other OPDs in conveying internet network disturbances, because the problems that often occur in delivering internet service information are still very ineffective and complaints are still limited to being delivered directly to the Head of Service and Administrator Officers so that potential forgot and re-checking of assignments by superiors is no longer carried out. So with the existence of an Information Loss information system it is very helpful for employees in conveying internet network disturbances. The purpose of this research is to be taken into consideration by the founder of the system in repairing and enhancing the Lost Network Application system using the EUCS method. Results Measurement of user satisfaction is based on 5 predefined dimensions, namely: Content, Accuracy, Format, Easy of Use, and Timeliness. Based on evaluation results. the total level of satisfaction for all dimensions felt by users of the IlangNetwork application using the EUCS model approach is 68.21% with a gap/difference of 31.79% meaning that the level of user satisfaction is in the satisfied category range of the five dimensions analyzed, 3 dimensions are in very satisfied category namely; content, accuracy, format and 2 dimensions which are in the dissatisfied category, namely; ease of use and timeliness.